2022
DOI: 10.1002/ps.7224
|View full text |Cite
|
Sign up to set email alerts
|

Triazole resistance in Aspergillus fumigatus exposed to new chiral fungicide mefentrifluconazole

Abstract: BACKGROUND Triazole resistance in the human fungal pathogen Aspergillus fumigatus has been a growing challenge in clinic treatment with triazole drugs such as itraconazole. The fast evolvement of triazole resistance in A. fumigatus in the ecosystem has drawn great attention, and there has been a possible link between the application of triazole fungicides in agriculture and triazole resistance in A. fumigatus. The change in susceptibility of A. fumigatus exposed to the new chiral triazole fungicide mefentriflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The overexpression of CcCYP51A and CcCYP51B also was associated with mefentrifluconazole resistance in Corynespora cassiicola . Overexpression of cyp51A , AtrF , AfuMDR1 , and AfuMDR4 were associated with the acquired mefentrifluconazole resistance in Aspergillus fumigatus with hereditary stability . This investigation discovered the L144F substitution in FpCYP51B in four mutants that exhibited resistance to mefentrifluconazole.…”
Section: Discussionmentioning
confidence: 78%
“…The overexpression of CcCYP51A and CcCYP51B also was associated with mefentrifluconazole resistance in Corynespora cassiicola . Overexpression of cyp51A , AtrF , AfuMDR1 , and AfuMDR4 were associated with the acquired mefentrifluconazole resistance in Aspergillus fumigatus with hereditary stability . This investigation discovered the L144F substitution in FpCYP51B in four mutants that exhibited resistance to mefentrifluconazole.…”
Section: Discussionmentioning
confidence: 78%
“…19 In the stereoselectivity of fungicide resistance, R-mefentrifluconazole exhibited stronger resistance in Aspergillus fumigatus. 20 On account of 17.73 times higher activity against Fusarium graminearum, R-(−)-prothioconazole induce F. graminearum into producing more DON. 21 In chiral amide fungicides, the enantioseparation mechanism of penflufen was explained by computational chemistry, 22 and S-penflufen was 54 times more toxic to Danio rerio and 148 times more toxic to R. solani.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In the stereoselectivity of fungicide resistance, R -mefentrifluconazole exhibited stronger resistance in Aspergillus fumigatus . On account of 17.73 times higher activity against Fusarium graminearum, R -(−)-prothioconazole induce F. graminearum into producing more DON .…”
Section: Introductionmentioning
confidence: 99%
“…Triazole fungicides occupy a significant position in the global fungicide market. , Triazole fungicides have excellent antifungal activity and can effectively control powdery mildew, rust, sheath blight, and leaf spot . Mefentrifluconazole is a new-generation triazole fungicide developed by BASF . Mefentrifluconazole has a unique isopropyl alcohol structure that effectively solves the problem of resistance to triazole fungicides .…”
Section: Introductionmentioning
confidence: 99%
“…Mefentrifluconazole has a unique isopropyl alcohol structure that effectively solves the problem of resistance to triazole fungicides . Studies have shown that mefentrifluconazole has excellent bioactivity against powdery mildew, leaf blight, sheath blight, and rice blast. , Currently, mefentrifluconazole is registered under the name Revysol in more and more countries and has broad application prospects.…”
Section: Introductionmentioning
confidence: 99%